Ageing of glass passivated TRIAC devices under thermal and electrical stress. (November 2020) - Buvat, Y.; Bouyssou, E.; Morillon, B.; Gautier, G.
Abstract: A new silicate glass passivation was studied on Metal-Dielectrics-Semiconductor structures to characterize the reliability performances of TRIAC devices. The presence of mobile ions was identified in the glass affecting the reliability performances. The addition of a semi-insulating passivation layer turns out to drastically improve the reliability performances of TRIAC devices. Highlights: Ageing of glass material using Metal Glass Semiconductor capacitor at wafer level and TRIAC device at die level Accumulation of mobile ions near the interface between the new glass and the silicon Semi-insulating passivation layer seems to trap mobile ions from accumulating near the glass-silicon interface. Very promising reliability performances obtained with the semi-insulating passivation layer.